Designing Public Kitchen in a Disaster Evacuation Site using the Pahl and Beitz Method - Rohimah, Anni; Saputra, Rahmat; Sulistyo, Suryo; Sartono, S; Soerahman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this study is to address the urgent needs at disaster evacuation sites, such as death, loss, injury, and displacement, by creating an emergency public kitchen. The methodology for designing this emergency kitchen involves an ergonomic approach that considers air circulation, necessary equipment, and supporting items like trash cans. The author follows the methods and design steps of Pahl and Beitz, which include four stages: planning and task explanation, product concept design, product shape design, and detail design. The results of this approach yield a new layout for an emergency kitchen that can support the logistical needs of disaster victims. This kitchen design can serve as a guide for universities and Muhammadiyah organizations to address the challenge of establishing public kitchens in disaster evacuation sites.